Utilization of Digital Terrain Model (DTM) from LiDAR data for flood inundation simulation due to Ciujung River overflow in Banten Province - Firmansyah, Yudi; Mahfudz, Mohamad; Nurtyawan, Rian (Universitas Pakuan, 2024)
Flood phenomena are natural disasters that are still difficult to predict due to climate change. Climate change has caused rainfall to become extreme, leading to floods as the water discharge exceeds river capacity. The Ciujung River is one of the major rivers in Banten Province. In 2012, the Ciujung River overflowed, cutting off access to the Tangerang-Merak Toll Road. This study utilizes a Digital Terrain Model (DTM) derived from LiDAR data and HEC-RAS software to simulate flood inundation due to the overflow of the Ciujung River in Banten. LiDAR data provides a high-resolution DTM, offering detailed and accurate topographic information. Using HEC-RAS, a hydraulic model was created to simulate water flow and potential flood inundation along the river. The simulation method refers to the Saint-Venant equations with an iterative procedure known as the standard step method. The simulation results show reliable flood depth and inundation spread as a reference for flood disaster mitigation planning. The final result of this study is a flood inundation map that provides a clear picture of flood risk levels along the Ciujung River, which can be used by local governments and other stakeholders for decision-making. From 12 flood inundation sample points, 60% were validated based on respondents' feedback. The area affected by flood hazards along the Ciujung River increased with rising water discharge, with the largest area being 109.06 hectares when the discharge reached 3000 m³/s.Fenomena banjir merupakan bencana alam yang masih sulit diprediksi akibat perubahan iklim. Perubahan iklim menyebabkan curah hujan menjadi ekstrem sehingga menyebabkan banjir karena debit air melebihi kapasitas sungai. Sungai Ciujung merupakan salah satu sungai besar yang ada di Provinsi Banten. Pada tahun 2012, Sungai Ciujung meluap sehingga memutus akses Tol Tangerang-Merak. Penelitian ini memanfaatkan Digital Terrain Model (DTM) yang berasal dari data LiDAR dan software HEC-RAS untuk melakukan simulasi genangan banjir akibat meluapnya Sungai Ciujung di Banten. Data LiDAR menyediakan DTM resolusi tinggi, menawarkan informasi topografi yang detail dan akurat. Dengan menggunakan HEC-RAS, model hidrolik dibuat untuk mensimulasikan aliran air dan potensi genangan banjir di sepanjang sungai. Metode simulasi mengacu pada persamaan Saint-Venant dengan prosedur iteratif yang dikenal dengan metode langkah standar. Hasil simulasi menunjukkan kedalaman banjir dan sebaran genangan yang dapat diandalkan sebagai acuan perencanaan mitigasi bencana banjir. Hasil akhir dari penelitian ini adalah peta genangan banjir yang memberikan gambaran jelas tingkat risiko banjir di sepanjang Sungai Ciujung, yang dapat digunakan oleh pemerintah daerah dan pemangku kepentingan lainnya dalam pengambilan keputusan. Dari 12 titik sampel genangan banjir, 60% tervalidasi berdasarkan masukan responden. Luas wilayah yang terkena bahaya banjir di sepanjang Sungai Ciujung bertambah seiring dengan meningkatnya debit air, dengan luas terluas 109,06 hektar dengan debit mencapai 3000 m³/s.